THE EFFECT OF PROJECT-BASED LEARNING APPROACH ON STUDENTS’ ACADEMIC ACHIEVEMENT: A MIXED META-METHOD - Shafiyu Jibril; Yavuz Topkaya; Veli Batdı (Educational Academic Research, 2024)
The main purpose of this study is to investigate the effect of a project-based learning approach on students’ academic performance through a mixed meta-method. For this reason, a dual methodological approach meta-analytical of quantitative data and meta-thematic of qualitative data were used in determining the effect size in quantitative dimension, while, in the qualitative dimension the positive and negative aspects together with the recommendation was determined. To this end, meta-analysis was conducted using data from 26 studies and meta-thematic from 8 studies. In order to determine the effect size, CMA and MetaWin were used and the effect size was calculated at a large level with the value of g =.83 [-.02; 1.68], and a significant difference of p˂.05. In the meta-thematic analysis, the effect of project-based learning was found to have a positive effect as well as a little negative impact on students’ academic performance. Recommendations were also provided through the participants’ views. In both the meta-analysis and meta-thematic analysis, the findings showed that the project-based learning approach owns a great effect on the students’ academic performance.